2001
DOI: 10.1074/jbc.m011424200
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic Effects of Smad2 VersusSmad7 Are Sensitive to Their Expression Level during Tooth Development

Abstract: Members of the transforming growth factor-␤ (TGF-␤

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 55 publications
0
23
1
Order By: Relevance
“…It was previously shown that Cas-L binds to R-Smad, Smad3, with being proteasomally degraded by Smad3, and that overexpression of Cas-L in A549 cells results in inhibition of transcriptional activity in TGF-b signaling (Liu et al, 2000). This discrepancy may be explained by that the cell typespecific abundance of subcellular downstream molecules in TGF-b signaling, including R-Smad/I-Smad ratio (Ito et al, 2001), SARA (Xu et al, 2000a) or Ski (Xu et al, 2000b), which differently regulate TGF-b signaling in a complex manner. Moreover, previous work identified a splice variant of Smad6 that is differentially regulated in diseased tissues and appears to be a TGF-b pathway activator, in contrast to wt Smad6 (Krishnan et al, 2001).…”
Section: Discussionmentioning
confidence: 63%
“…It was previously shown that Cas-L binds to R-Smad, Smad3, with being proteasomally degraded by Smad3, and that overexpression of Cas-L in A549 cells results in inhibition of transcriptional activity in TGF-b signaling (Liu et al, 2000). This discrepancy may be explained by that the cell typespecific abundance of subcellular downstream molecules in TGF-b signaling, including R-Smad/I-Smad ratio (Ito et al, 2001), SARA (Xu et al, 2000a) or Ski (Xu et al, 2000b), which differently regulate TGF-b signaling in a complex manner. Moreover, previous work identified a splice variant of Smad6 that is differentially regulated in diseased tissues and appears to be a TGF-b pathway activator, in contrast to wt Smad6 (Krishnan et al, 2001).…”
Section: Discussionmentioning
confidence: 63%
“…This result suggested that STAT-1 plays a role in the regulation of Muc4/SMC expression. Additionally, SMAD7 was selected as a possible candidate in mediating the IFN-␥ signal and regulating the TGF-␤ induced inhibition of Muc4/SMC expression (17,19,23,24). Antisense inhibition assays revealed that SMAD7 was required for blocking the effect of TGF-␤ on Muc4/SMC expression (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The phosphorylated STAT forms a homodimer that can translocate to the nucleus to regulate gene transcription (18). TGF-␤ and IFN-␥ have been shown to have antagonistic effects on cellular functions (16,19). Recent studies have shown that IFN-␥ acts on the TGF-␤ pathway via Jak-1 and STAT-1 to induce SMAD7 expression, which inhibits TGF-␤ R-SMAD phosphorylation and its downstream events (16).…”
Section: Muc4/smcmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the role of each of them in tooth development is largely elusive, since most knockout mice die before tooth development begins. Using an in vitro organ culture and antisense approach, Chai and his colleagues were able to show that attenuation of Smad2 and Smad7 expression result in abnormal tooth development, indicating that the effectiveness of TGF-β signaling in tooth development is highly sensitive to the level of Smad gene expression [59].…”
Section: Bmpsmentioning
confidence: 99%